1984
DOI: 10.1055/s-2008-1054565
|View full text |Cite
|
Sign up to set email alerts
|

Eine neue Funktion des nicht-pigmentierten Epithels der Ziliarkörperfortsätze bei der Kammerwasserproduktion

Abstract: The invagination of the optic vesicle has, as one of its consequences, the apposition of the apices of the nonpigmented and pigmented epithelia of the ciliary processes of the eye. There are well developed intercellular ciliary "channels" formed at the apices of these cells. Embryologically the ciliary epithelia are homologous to the epithelia of the choroid plexus, a characteristically differentiated ependyma. These epithelial cells have a polarity. For example, the supranuclear region of the nonpigmented epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…There is a potential space between the two epithelial layers, called "ciliary channels". The aqueous humor may be secreted into this space after beta-adrenergic agonist stimulation, but this notion requires additional studies [20].…”
Section: Innervationmentioning
confidence: 99%
“…There is a potential space between the two epithelial layers, called "ciliary channels". The aqueous humor may be secreted into this space after beta-adrenergic agonist stimulation, but this notion requires additional studies [20].…”
Section: Innervationmentioning
confidence: 99%
“…After topical application of the adenylate stimulator forskolin [29], Fujita et al [30] found a striking enlargement of the ciliary channels in the anterior portion of the rabbit ciliary body. In this respect they discuss fluid reabsorption from the posterior chamber and transport of solutes and molecules into the ciliary channels by the nonpigmented epithelium.…”
Section: Discussionmentioning
confidence: 99%